In vitro three-dimensional coculturing poly3-hydroxybutyrate-co-3-hydroxyhexanoate with mouse-induced pluripotent stem cells for myocardial patch application. (March 2016) - Shijun, Xu; Junsheng, Mu; Jianqun, Zhang; Ping, Bo
Identifying a suitable polymeric biomaterial for myocardial patch repair following myocardial infarction, cerebral infarction, and cartilage injury is essential. This study aimed to investigate the effect of the novel polymer material, poly3-hydroxybutyrate- co -3-hydroxyhexanoate, on the adhesion, proliferation, and differentiation of mouse-induced pluripotent stem cells in vitro. Mouse-induced pluripotent stem cells were isolated, expanded, and cultured on either two-dimensional or three-dimensional poly3-hydroxybutyrate- co -3-hydroxyhexanoate films (membranes were perforated to imitate three-dimensional space). Following attachment onto the films, mouse-induced pluripotent stem cell morphology was visualized using scanning electron microscopy. Cell vitality was detected using the Cell Counting Kit-8 assay and cell proliferation was observed using fluorescent 4', 6-diamidino-2-phenylindole (DAPI) staining. Mouse-induced pluripotent stem cells were induced into cardiomyocytes by differentiation medium containing vitamin C. A control group in the absence of an inducer was included. Mouse-induced pluripotent stem cell survival and differentiation were observed using immunofluorescence and flow cytometry, respectively. Mouse-induced pluripotent stem cells growth, proliferation, and differentiation were observed on both two-dimensional and three-dimensional poly3-hydroxybutyrate- co -3-hydroxyhexanoate films. Vitamin C markedly improved the efficiency of mouse-induced pluripotent stem cells differentiation into cardiomyocytes on poly3-hydroxybutyrate- co -3-hydroxyhexanoate films. Three-dimensional culture was better at promoting mouse-induced pluripotent stem cell proliferation and differentiation compared with two-dimensional culture.